The effect of health promotion on primary health care services: an analysis of primary health care policy - Olofinbiyi, Olunike Blessing (ScienceRise: Medical Science, 2022)
Health promotion is the best way to prevent mental illness and other illnesses in the community. However, the high rate of corruption and embezzlement of funds has impeded the effectiveness of health promotion in Primary health care system in Nigeria. More so, health promotion is the best way to alleviate diseases and prevent diseases. However, nearly all the health care workers are aware of the benefits of health promotion but to implement it is the problem. The aim: to examine the effect of health promotion on primary health care service through the analysis of Primary Health Care policy. Method: this study was guided by a pragmatic paradigm. The pragmatist paradigm is highly essential to this study because it emphasizes the link between action and truth. It is also ideal for this study as it advocates for mixed methods that are in line with ethnographic research approach to provide the best understanding of a research problem. Furthermore, pragmatic paradigm was adopted for this study and this paradigm encourages the study to combine two research methods (qualitative and quantitative) to achieve quality research findings. In this study a non-experimental, exploratory-descriptive design was used to analyse the quantitative aspect of the national health policies on primary health care service delivery in Nigeria. While ethnographic method analysed the qualitative aspect of the study perfectly. Result: out of three hundred respondents, majority of them revealed that bad leadership is the main reason why health promotion is not effective. While majority of the participants opined that we lack good leaders. The study hereby emphasized more on why the Government is not working on the effectiveness of health promotion in PHC and the findings showed that bad leadership is the main factor that is causing the ineffectiveness of health promotion in PHC and when the respondents were questioned on what to do to ensure a more effective health promotion in the community, majority (34.7 %) of the respondents opined that the community members should be involved actively at every stage while (33.3 %) of the respondents revealed that there is need for active involvement of other essential sectors in formulation and implementation of PHC policy to ensure a permanent change. Conclusion: this study shows that poor health promotion in Primary health care is having negative effect on the health of children, adolescents, adults, and old ones. This study here by recommends that the policy makers and the government should eradicate corruption and embezzlement of funds in all sectors especially in primary health care